Reversing Historical Injustices, Facing New Legal Challenges: Lithuanian Liberation and post-Soviet Transition (1987-2004) - Rogers, Monika (Institute of National Remembrance Review, 2025)
The aim of this article is to reconstruct the process of the restoration of Lithuania’s independence in the context of the fall of Communism and the transition to democracy. The chronological boundaries are the year 1987 (the first mass demonstration in Lithuania after the suppression of so-called Kaunas Spring in 1972) and the early 2000s (symbolic years marking full Lithuanian transatlantic integration, joining the EU and NATO). Special attention will be given to the social transition, followed by almost a uniform demand for restoring the rule of law and rebuilding historically-threatened justice. Law and justice were the essential planes of Lithuanian post-Soviet transformation – but in its historiography these dimensions are receiving less attention than the economic or political transition.